2018
DOI: 10.1152/ajpheart.00097.2018
|View full text |Cite
|
Sign up to set email alerts
|

High salt intake shifts the mechanisms of flow-induced dilation in the middle cerebral arteries of Sprague-Dawley rats

Abstract: The goal of the present study was to examine the effect of 1 wk of high salt (HS) intake and the role of oxidative stress in changing the mechanisms of flow-induced dilation (FID) in isolated pressurized middle cerebral arteries of male Sprague-Dawley rats ( n = 15-16 rats/group). Reduced FID in the HS group was restored by intake of the superoxide scavenger tempol (HS + tempol in vivo group). The nitric oxide (NO) synthase inhibitor N-nitro-l-arginine methyl ester, cyclooxygenase inhibitor indomethacin, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 76 publications
2
43
0
Order By: Relevance
“…Similarly, we previously demonstrated increased leukocytes' reactive oxygen species production after HS intake in normotensive Sprague-Dawley rats [12]. Thus, it may be suggested that leukocyte-endothelial adhesion in response to HS loading is multifactorial, and the role of the RAS becomes apparent along with progression of vascular damage [12, 14].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, we previously demonstrated increased leukocytes' reactive oxygen species production after HS intake in normotensive Sprague-Dawley rats [12]. Thus, it may be suggested that leukocyte-endothelial adhesion in response to HS loading is multifactorial, and the role of the RAS becomes apparent along with progression of vascular damage [12, 14].…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, impaired suppressive Treg function during HS load contributes to augmented Th1/Th17-mediated inflammation in autoimmune disease [11]. Interestingly, excessive salt intake has been linked to increased oxidative stress [1214], aggravated inflammation, and pathophysiological differentiation of monocytes leading to organ damage even in treated hypertensive patients, suggesting a blood pressure-independent effect [1518].…”
Section: Introductionmentioning
confidence: 99%
“…Lipids extraction in plasma samples was performed as previously described [ 26 ]. The concentrations of LOOH were calculated using the molar absorptivity of the complex [FeNCS] 2+ formed per mol of LOOH, 58,440 M −1 cm −1 , at 500 nm [ 27 , 28 ]. Measurements were performed in the Laboratory for Radiation Chemistry and Dosimetry, Ruđer Bošković Institute, Zagreb, Croatia.…”
Section: Methodsmentioning
confidence: 99%
“…Blood pressure measurement was performed using established protocols, as previously described [ 18 , 29 , 54 , 55 ]. Briefly, pressure values were measured using the Spacelabs Medical system (Spacelabs Medical, Inc., Redmond, WA, USA) using the PE-50 catheter inserted into the left femoral artery.…”
Section: Methodsmentioning
confidence: 99%
“…The Western blot was made according to the established method of our laboratory [ 9 , 55 ]. The same Western blot protocol was used to determine the COX-1, COX-2, iNOS, HIF-1α, VEGF and CYP2c11 protein expression in the rat aortas, deeply frozen immediately after isolation.…”
Section: Methodsmentioning
confidence: 99%